Main Transformer for B0-B0-B0 AC-driving Electric Locomotive - PENG Xiang (机车电传动)
Main technical parameters, design principle and structure features of main transformer for B0-B0-B0 AC drive electric locomotive were introduced, as well as the related protection and monitoring device of the transformer. With application in Uzbekistan locomotive, all performance index of main transformer was shown completely satisfy operation requirements.